Whether Modular Capacity Building Tools are Effective in Empowering Self Help Groups (SHGs) in Rural India? - Sangeetha, V.; Sharma, Nishi; Wason, Monika; Singh, Premlata; Padaria, R. N. (International Journal of Bio-resource and Stress Management, 2016)
Self Help Groups (SHGs) have become the most important grass root level institutions in India. Capacity building of these groups in different areas is increasingly becoming important to make these institutions potential means for economic development of the country. Financial education and Information and Communication Technology (ICT) is most important for the SHGs as it will lead to positive change towards their financial attitude, strengthen their financial capabilities to make sound decisions, lead them to greater financial access and aid in utilizing and sharing knowledge for socio-economic development of the group members. With this background, an attempt has been made to analyse the role of ICT and Financial Management (FM) modules in empowering rural women SHGs. In the present study, modules on ICT and FM were designed and then validated among fifty women SHG members and their change in knowledge level was assessed. It was found that average knowledge score of the members on ICT was 9.26 before and 16.94 after training and for financial management, it was 21.32 and 39.80 respectively. The results showed that an overall assessment score was 3.8 for ICT module and 4.2 for financial management. In both the modules, an overall utility was rated highest with mean score 4.3 and 4.9 for ICT and FM modules respectively. The study indicated the importance of capacity building modules and also the training which played a critical role in knowledge enhancement of rural women in using ICT tools and understanding financial management.